Collective action and agroindustries - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Two fundamental global economic tendencies have caused a shift in interest towards promoting rural agroenterprises and agroindustrialization to combat rural poverty. Increasing income levels and demographic changes, i.e. increased female labor force participation, has fueled demand for high-value and processed products. Structural adjustment and liberalization policies have reduced barriers to trade globally and allowed markets to reach even the most isolated rural areas.